Zaangażowanie pracowników a doskonalenie jakości - Bugdol, Marek (Employees' Commitment and Quality Improvement, 2008)
The article presents selected issues connected with employees' commitment. The typology of commitment has been presented, and the characteristics and advantages of commitment, as well as its role in TQM philosophy and in service quality improvement have been discussed. The author discusses commitment in the category of an organization value. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 354-364